Pythium ultimum and Phytopythium vexans, the Potential Pathogen Isolated from Potato Rhizosphere in Central Java, Indonesia - Karmila, Miratun; Widiastuti, Ani; Wibowo, Arif; Suryanti, Suryanti (Jurnal Fitopatologi Indonesia, 2022)
Phytophthora and Pythium are a group of Oomycetes that are widely associated with diseases in potato plants. Therefore, this study was conducted to identify the Oomycetes associated with the rhizosphere of infected potato plants showing leaf blight. Four isolates were collected from four regions in Central Java (UGM_St_TM, UGM_St_BK, UGM_St_BNJ, and UGM_St_KJ, the isolate from Temanggung, Bakal, Banjarnegara, Kejajar respectively), and UGM_St_NG isolate as culture collection from Laboratory of Plant Pathology. Molecular identification of all isolates was carried out using the internal transcribed spacer (ITS1/ITS4), nuclear large-ribosomal subunit (LSU), and cytochrome C oxidase subunit 1 (COX1) gene markers. Based on the results, the isolates UGM_St_TM, UGM_St_BK, and UGM_St_BNJ were identified as Phythium ultimum while UGM_St_KJ and UGM_St_NG isolate were identified as Phytopythium vexans.